Physicians’ Views on the ‘Institutional Practice’ Proposed by the Government of Bangladesh - Aktar, Shabnaj; Refat, Md Nazmul Hassan; Nurunnabi, Abu Sadat Mohammad; Islam, Rezwana; Tasmia, Gul E Noor; Kanon, Sucheta; Sultana, Rezwana; Das, Mukta; Roman, Md Abdullah Al Kafi (Bangladesh Journal of Medical Education, 2026)
Background: Initiative has been taken by the Government of Bangladesh to establish ‘institutional practice’ in government hospitals after regular working hour to bring those patients under the mainstream of healthcare, who often face financial hardship to access the same service from private healthcare facilities through out-of-pocket expenditure. Objective: This study examined physicians’ views on the ‘institutional practice’ in terms of its opportunity, compatibility and complexity. Methods: This cross-sectional, descriptive study was conducted in three urban tertiary level public hospitals in Dhaka, Bangladesh. A total of 313 physicians of different specialties were selected through convenience sampling. Data was collected using a pre-tested, semi-structured questionnaire. A 5-point Likert scale was used to measure physician’s views towards institutional practice. Results: The mean age of the participating physicians was 38.4±7.10 years. 62% of the physicians were male and 38% were female. The majority (55.9%) of physicians agreed that institutional practices can ensure healthcare for more patients. 46.6% agreed that this arrangement will serve as a source of additional income for health professionals. 59.7% agreed institutional practices can reduce out-of-pocket costs for patients. However, there were concerns about adequate compensation within institutional practices. 44.7% and 42.5% disagreed with the consultation and surgery fees respectively, as proposed by the government. Overall, 55.9% opined that this will increase their workload, while 38.7% anticipated difficulties in monitoring revenues. Conclusion: Although a large portion of physicians disagreed with the fee structure and duty schedule, the majority agreed with the prospective opportunities through adoption of institutional practice. The study findings can be utilized to modify and strengthen the policies to implement an effective ‘institutional practice’. BJME: Vol.-17, Issue-01, January, 2026: 60-68